Impact of the grassland ecological compensation policy on pastoral production efficiency—evidence from pastoral China - Fang Ju; Wenjie Ouyang; Chengtao Zhang; Jianjun Zhang (PLoS ONE, 2025)
The impact of the Grassland Ecological Compensation Policy (GECP), which protects grassland ecology while promoting the transformation and improvement of grassland animal husbandry, on pastoral production efficiency is among the important indicators for evaluating the sustainable development of animal husbandry, and it directly affects the economic benefits of herders. In this study, based on field questionnaire data from 468 herders in the pastoral areas of the Inner Mongolia Autonomous Region of China, a two-stage semi-parametric DEA model and a mediated effect model were used to measure herders’ pastoral production efficiency and analyze the effect and influence mechanism of the GECP on herders’ pastoral production efficiency, respectively. The results of the study show that (1) the overall pastoral production efficiency of herders in Inner Mongolia is low, with a mean value of 0.43, which is caused mainly by low pure technical efficiency. (2) The factors that have a significant positive effect on the herding efficiency include the number of years of education of the head of the household, whether the head of the household has received technical training, the percentage of herding income from herding, the number of herding machines available, the evaluation of herding socialized services and whether pasture is rented or owned. (3) The realization of appropriate-scale management by herders plays a role in mediating herders’ pastoral production efficiency. The realization of moderate-scale management by herders has a partial intermediary effect on the process through which the GECP affects herders’ pastoral production efficiency, and the direct effect of this policy on the pastoral production efficiency of large-scale herders is significantly greater than that on small-scale herders. Based on the above conclusions, suggestions are proposed for improving support policies that offer ecological bonuses, demonstrating and popularizing breeding technology, and guiding moderate-scale management.